Experimental and numerical investigations of a segmental masonry arch subjected to horizontal settlements - Masciotta, Maria Giovanna (2020)
Settlements represent one of the main causes of collapse in arched structures. The stiffness degradation and strength reduction associated with these slow long-term movements are reflected in changes of the dynamic properties of the system (frequencies, mode shapes and damping ratios). The correct dynamic characterization of the nonlinear behaviour of masonry arches undergoing supports settlements is therefore fundamental to timely detect the occurrence of serious damage mechanisms and prevent unexpected failures. This paper aims to investigate the dynamic behaviour of a segmental masonry arch subjected to stepwise horizontal displacements of one support. To this end, output-only dynamic identification techniques are first used to estimate the experimental dynamic properties of the system under progressive damage scenarios. Then, a numerical procedure coupling linear perturbation and modal analysis is applied to evaluate frequencies and mode shapes of the arch, taking into account the actual crack distribution induced by the settlements. The combination of experimental and numerical investigations allows to explore in detail the dynamics of the settled masonry arch as well as its potential collapse mechanism.